Cooperative Use of VCD and XRD for the Determination of Tetrahydrobenzoisoquinolines Absolute Configuration: A Reliable Proof of Memory of Chirality and Retention of Configuration in Enediyne Rearrangements. Issue 12 (13th August 2013) - Mondal, Shovan; Naubron, Jean‐Valère; Campolo, Damien; Giorgi, Michel; Bertrand, Michéle P.; Nechab, Malek
ABSTRACT The absolute configurations (AC) of azaheterocylic compounds resulting from the cascade rearrangement of enediynes involving only light atoms were unambiguously assigned by the joint use of vibrational circular dichroism (VCD) and copper radiation single crystal X‐ray diffraction (XRD). These AC determinations proved that the rearrangements of enediynes proceeded with memory of chirality and retention of configuration. Chirality 25:832–839, 2013. © 2013 Wiley Periodicals, Inc.